Salmonella enteritidis phage type 4 isolates more tolerant of heat, acid, or hydrogen peroxide also survive longer on surfaces. - Humphrey, T J (1995)
In a comparative study of different Salmonella enteritidis phage type 4 isolates we found that those isolates with enhanced heat tolerance also survived better than isolates that were heat sensitive either at pH 2.6, in 10 mM H2O2, or on surfaces. Culture to the stationary phase increased the heat tolerance of all isolates and the acid and H2O2 tolerance of heat-tolerant isolates. With heat-sensitive isolates, however, extended culture had no impact on survival in H2O2 and only a marginal impact on acid tolerance. The growth phase had no appreciable impact on the surface survival of any of the isolates.